2022
DOI: 10.1093/scan/nsac005
|View full text |Cite
|
Sign up to set email alerts
|

Inter-brain neural mechanism underlying turn-based interaction under acute stress in women: a hyperscanning study using functional near-infrared spectroscopy

Abstract: With the ever-changing social environment, stress has exerted the substantial influence on the social interaction. The present study examined the underlying cognitive and neural mechanism on how acute stress affected the real-time cooperative and competitive interaction with four hypothesized path models. We used the hyperscanning technique based on a functional near-infrared spectroscopy (fNIRS) device to examine brain-to-brain coherence within the dyads engaging Pattern Game (PG) under acute stress manipulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 93 publications
1
9
0
1
Order By: Relevance
“…Based on the WTC analyses of the two-time series generated by each dyad, we focused on the frequency band between 6.9 s and 7.3 s that was more sensitive to our task (Figure 3). This frequency band did not include high-and low-frequency noise, such as physiological noises related to Mayer waves (0.1 Hz), respiration (~0.2-0.3 Hz) and cardiac pulsation (about 1 Hz) [39,40]. The average coherence in this band for each task condition was calculated by subtracting the average coherence during the rest session from that during the task session.…”
Section: Fnirs Data Analysismentioning
confidence: 99%
“…Based on the WTC analyses of the two-time series generated by each dyad, we focused on the frequency band between 6.9 s and 7.3 s that was more sensitive to our task (Figure 3). This frequency band did not include high-and low-frequency noise, such as physiological noises related to Mayer waves (0.1 Hz), respiration (~0.2-0.3 Hz) and cardiac pulsation (about 1 Hz) [39,40]. The average coherence in this band for each task condition was calculated by subtracting the average coherence during the rest session from that during the task session.…”
Section: Fnirs Data Analysismentioning
confidence: 99%
“…A vector auto-regressive model was established to calculate EC values, and the best model order ‘p’ was identified using the Akaike [ 40 ] and the Bayesian Information Criterion [ 41 , 42 ]. For two continuous time series x(t) and y(t), if the accuracy of the model using the past information of y(t) and x(t) is higher than the model only using x(t), it can be considered that y(t) is assumed to cause x (t) (there is an information flow from y(t) → x(t)) [ 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…To determine the appropriate sample size, a statistical power analysis was performed based on a medium effect size (Cohen's f = 0.25), which is frequently employed in previous research (Cohen, 1988;Harel et al, 2023;Huang et al, 2023;Zhao et al, 2022). The results suggested that a sample size of 54 participants was deemed necessary to detect the hypothesized effect at α = .05 and β = .95 (Faul et al, 2007).…”
Section: Participantsmentioning
confidence: 99%